Emergency certified teachers' motivations for entering the teaching profession: Evidence from Oklahoma - Tyler J. Mobra; Daniel E. Hamlin (Arizona State University, 2020)
The use of emergency certification to fill teaching vacancies has increased in many school districts across the United States. Prior research suggests that teachers' underlying motivations for entering the profession are associated with student outcomes, but very little is known about the motivations of emergency certified teachers who enter the profession in a less systematic fashion than traditionally certified teachers. To understand emergency certified teachers' rationales for entering teaching, we interviewed 30 emergency certified teachers in Oklahoma where emergency certification has risen sharply. Findings indicate that emergency certified teachers articulate intrinsic motivations for entering the profession that are similar to those commonly identified by traditionally certified teachers. However, emergency certified teachers also report motivations that seemed to be markedly different, such as using teaching as a contingency employment option or wanting to test out the profession before committing to it. This study raises important policy questions about the use of emergency certification as a strategy for filling teaching vacancies.